Phytochemical Profiling and Biological Activities of Extracts from Bioreactor-Grown Suspension Cell Cultures of Schisandra henryi - Karolina Jafernik; Adam Kokotkiewicz; Michał Dziurka; Aleksandra Kruk; Anna Hering; Krzysztof Jędrzejewski; Piotr Waligórski; Piotr Graczyk; Paweł Kubica; Justyna Stefanowicz-Hajduk; Sebastian Granica; Maria Łuczkiewicz; et al. (Molecules)
Plant biotechnology creates opportunities for the cultivation of plants regardless of their natural habitats, which are often protected or difficult to access. Maintaining suspension cell cultures in bioreactors is an advanced part of biotechnological research that provides possibilities for obtaining plant tissue on a large scale. In this study, the suspension culture cultivation of a Chinese endemic plant, Schisandra henryi, in a stirred tank bioreactor was elaborated for the first time. The phytochemical profile of the tissue extracts was determined with UHPLC-MS/MS for the lignans (fifteen dibenzocyclooctadiene lignans, one aryltetralin lignan, and two neolignans) and UHPLC-DAD-ESI-MS3 for the phenolic compounds (procyanidins and their derivatives and catechin). The maximum total lignan content of 1289 µg/100 g DW was detected for the extracts from suspensions cultured in a bioreactor for over 10 days. For the phenolic compounds, catechin was the dominant compound (390.44 mg/100 g DW). The biological activity of the extracts was tested too. To determine antioxidant potential we used DPPH (2,2-diphenyl-1-picrylhydrazyl), ABTS (2,2′-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid), Molybdenum reduction, and β-carotene bleaching tests. The inhibition activity of the S. henryi extract on the enzymes responsible for skin aging, hyaluronidase and tyrosinase, was assessed with spectrophotometry. The cytotoxic activity of the extracts was estimated on human ovarian SKOV-3, cervical HeLa, and gastric AGS cancer cells and non-cancer, normal fibroblasts by an MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay. The results showed the great potential of the obtained cell biomass extracts. The results of the antioxidant tests indicated their strong ability to reduce the level of free radicals, similarly to that of ascorbic acid, as well as the weak capacity to protect lipids from oxidation. Moreover, anticancer potential, particularly on the cervical and gastric cancer cells, was confirmed too.